The Silage Quality of Pennisetum purpureum Cultivar Gamma Umami Mixed with Calliandra calothyrsus and Lactiplantibacillus plantarum - Mudhita, I. K.; Putra, R. A.; Rahman, M. M.; Widyobroto, B. P.; Agussalim; Umami, N. (Tropical Animal Science Journal, 2024)
This study aimed to determine the effect of Calliandra calothyrsus supplementation and inoculation of Lactiplantibacillus plantarum (L. plantarum) on Penisetum purpureum cv. Gamma Umami grass fermentative and chemical quality and nutrient degradability. The study used a completely randomized design with 3 × 3 factorial patterns. The first factor was Calliandra supplementation levels at 10%, 20%, and 30%; the second was L. plantarum inoculation levels at 0%, 2%, and 4%. The variables measured included chemical fermentation profiles, chemical composition, and rumen fermentation and degradability parameters. The result showed that a higher level of C. calothyrsus supplementation concomitant increased silage pH and NH3-N concentration (p<0.05), while L. plantarum inoculation significantly decreased the silage pH and ammonia concentration (p<0.05). The silage contents of dry matter, organic matter, crude protein, and ether extract in silage significantly (p<0.05) increased. Inoculation of L. plantarum decreased (p<0.05) crude fiber, ether extract, and total tannin content of silage. The total volatile fatty acids, acetate, propionate concentrations, and rumen microbial protein synthesis were significantly increased with Calliandra supplementation (p<0.05). L. plantarum inoculation treatment only increased the proportion of acetate (p<0.05) and tended to increase the volatile fatty acids of rumen fluid, the proportion of acetate, propionate, and butyrate. The rumen ammonia concentration decreased with Calliandra supplementation and L. plantarum inoculation. It is concluded that 30% Calliandra supplementation and 2% L. plantarum inoculation and their combination were the treatments that produced the best chemical fermentation, rumen fermentation, and degradability parameters.